Crime and police in India (upto 1861) - "Gupta, Anandswarup" (Delhi, 2007)
The subject of the thesis was "Police Reform in India under the Company's Rule, 1757-1857". Historically, 1861, and not 1857, marks a water-shed in the story of the Indian Police.
Keywords: IPS as an author